Viral, host and environmental factors that favor anthropozoonotic spillover of coronaviruses: An opinionated review, focusing on SARS-CoV, MERS-CoV and SARS-CoV-2 - de Silva, PG (2021)
Environmental factors play a key role in the zoonotic transmission of emerging pathogenic viruses as mankind is constantly disturbing wildlife's ecosystems usually by cutting down forests to build human settlements or by catching wild animals for food, which deprives the viruses of their natural hosts and gives them opportunity to infect humans. In December 2019, a new coronavirus emerged from bats and was named SARS-CoV-2 by the International Committee for Taxonomy of Viruses, and the disease it causes named COVID-19 by the World Health Organization. Disease outbreaks such as SARS in 2002–2003, MERS in 2012 and the current COVID-19 pandemic are the result of higher mutation rates of coronaviruses and their unique capacity for genetic recombination, resulting in adaptations that make them more suitable to cross the species barriers and infect other species. This ability for host switching and interspecies infection is often attributed to the great diversity of these viruses, which is a result of viral and host factors such as the low fidelity of their RNA-dependent RNA polymerase, the high frequency of their homologous RNA recombination, and the adaptation of the S protein to bind host receptors like the angiotensin converting enzyme 2 (ACE2) in the case of SARS-CoV and SARS-CoV-2, and dipeptidyl peptidase 4 (DDP4) in MERS-CoV. This review presents an overview of the zoonotic transmission of SARS, MERS and COVID-19, focusing on the viral, host and environmental factors that favor the spillover of these viruses into humans, as well as the biological and ecological factors that make bats the perfect animal reservoir of infection for these viruses.